The Impacts of Urban Manufacturing Agglomeration on the Quality of Water Ecological Environment Downstream of the Three Gorges Dam - Huang, Can; Li, Xiao-Fan; You, Zhe (Frontiers in Ecology and Evolution, 2021)
As an important way to promote economic growth and to improve ecological environment quality, industrial agglomeration strategy has been widely accepted and implemented in various regions of China. In theory, industrial agglomeration is conducive to reducing pollution emissions. However, this needs to be tested in reality. The purpose of this paper is to test the impacts of manufacturing industry agglomeration on the quality of water ecological environment in 17 prefecture-level cities in the downstream of the Three Gorges Dam. Therefore, a theoretical model was established to test the direct and indirect effects. Empirically results show that the direct effect of manufacturing agglomeration on the quality of water ecological environment is -0.426, which provides statistical evidence for the important role of manufacturing agglomeration in improving the quality of water ecological environment. The indirect effect of manufacturing agglomeration on NH3-N is 0.118% through technological innovation, the indirect effect on NH3_N is 0.114% through economic growth, and the indirect effect on NH3_N is 0.254% through industrial structure. Due to the low overall level of the manufacturing industry and its reliance on dirty technologies, the indirect effects of industrial agglomeration are not conducive to improving the quality of the water ecological environment. Therefore, it is necessary to establish a long-term mechanism to promote the evolution of the regional economy along a path that is conducive to the improvement of the water ecological environment.